Carcass traits of crossbred (Landrace × Desi) barrows reared with different floor space allowances under intensive system - KASWAN, SANDEEP; PATEL, B H M; SINGH, MUKESH; DUTT, T; GAUR, G K; KAMAL, REENA; GODARA, A S U SINGH (The Indian Journal of Animal Sciences, 2016)
Present study assessed the effect of floor space allowances on carcass traits of crossbred (Landrace × Desi) barrows in Indian conditions. Crossbred barrows (36) were reared with 3 different floor space allowances (12 each) having group size of 4 pigs/pen. One group (TIS) was provided floor space as per Indian Standards (0.9, 1.35 and 1.8 m2/pig for weaner, grower and finisher stages, respectively) specifications, while other two groups with 33% (T2/3) and 50% (T1/2) reduced floor space allowances. Pigs were reared up to 29 weeks of age. Final weight of pigs did not differ significantly among the groups. Six animals from each group were slaughtered. None of the major economic carcass traits, viz. carcass weight, dressing %, back fat thickness (BFT), loin eye area (LEA), estimated lean meat percentage etc. was adversely affected. Major cut-up parts, share of edible as well as inedible offal and composition of pork (moisture, CP and EE) also did not differ among groups. It indicates scope of 50 % reduction in floor space allowance for pig production in India without affecting final body weight and major carcass characteristics.